The future is now: pioneering transformative approaches in higher education within creative fields - Anna Maria Ranczakowska; Kristina Kuznetsova-Bogdanovitsh (European Journal of Cultural Management and Policy)
This study investigates transformative approaches in arts and arts management education, highlighting the urgency for adaptive pedagogies in response to the unprecedented disruptions caused by recent global crises. The impact of these crises has profoundly affected the arts and cultural sectors, emphasising the need for higher education to equip students with skills to navigate and lead through complex and evolving cultural, social and economical landscapes. Our research focuses on immersive learning experiences and transformative learning theories as crucial methodologies in fostering essential future skills like adaptability, critical thinking, and innovative problem-solving in higher education. By integrating transformative learning theory and UNESCO’s model of future skills, we explore how such educational frameworks can profoundly influence students’ abilities to address societal transitions effectively. This study draws on qualitative data from immersive learning experiences in arts universities and provides empirical insights into the pedagogical effectiveness of combining transformative learning with hands-on, real-world engagement. The findings advocate for an educational paradigm that not only transfers knowledge but also significantly enhances the resilience and inclusivity of future arts professionals. This research contributes to the discourse on higher education’s role in cultivating creative leaders adept at navigating transitions towards more sustainable and inclusive cultural landscapes.